Enterprise survival in the high-tech community: persuasion and power in board decisions. Issue 4 (5th January 2021) - Yitshaki, Ronit; Gimmon, Eli; Khavul, Susanna
Abstract : Purpose: This study aims to examine the extent to which board size, the use of power by venture capital investors and entrepreneurs' interpersonal tactics such as persuasion to sway board decisions, influence the long-term survival of start-ups. Design/methodology/approach: This study used a mixed-methods approach. The quantitative part is based on data collected from 179 chief executive officers (CEOs) of high-tech start-ups community financed by venture capitalists (VCs) in Israel of which 59 did not survive. To achieve a better understanding of these findings, semi-structured interviews with 12 entrepreneurs were conducted. Findings: Smaller boards were positively associated with venture survival. The use of power by VC investors positively influenced start-up survival. CEO persuasion had a negative effect on venture survival; however, its interaction with board size suggests that it had a lesser effect on very small boards. Practical implications: Although investors' control over decision-making contributes to long-term survival, entrepreneurs should be aware of the possible detrimental effects of exercising a high level of persuasion in board processes. The findings also suggest that a small board size is preferable for start-up survival. Originality/value: Exploring the effect of board processes on venture survival is considered complex. A unique sample of high-technology start-ups consisting of both surviving and failed start-ups was analyzed to explore the effects of persuasion and power in board processes.